2016
DOI: 10.1513/annalsats.201504-241oc
|View full text |Cite
|
Sign up to set email alerts
|

Survival among Never-Smokers with Lung Cancer in the Cancer Care Outcomes Research and Surveillance Study

Abstract: Rationale: Differences in patient characteristics and outcomes have been observed among current, former, and never-smokers with lung cancer, but most prior studies included few never-smokers and were not prospective. Objectives:We used data from a large, prospective study of lung cancer care and outcomes in the United States to compare characteristics of never-smokers and smokers with lung cancer and to examine survival among the never-smokers.Methods: Smoking status at diagnosis was determined by selfreport a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 31 publications
5
25
0
Order By: Relevance
“…The present study confirms the findings from previous studies that adenocarcinoma and EGFR-mutations are overrepresented among lung cancer patients without a history of smoking [6,7,9,11,[14][15][16][17][18][19][20][21][22][24][25][26][41][42][43]. To the best of our knowledge, this was the first nationwide Nordic populationbased study finding a higher proportion of EGFR-mutations in never-smokers compared to ever smokers.…”
Section: Tumour Characteristicssupporting
confidence: 92%
See 3 more Smart Citations
“…The present study confirms the findings from previous studies that adenocarcinoma and EGFR-mutations are overrepresented among lung cancer patients without a history of smoking [6,7,9,11,[14][15][16][17][18][19][20][21][22][24][25][26][41][42][43]. To the best of our knowledge, this was the first nationwide Nordic populationbased study finding a higher proportion of EGFR-mutations in never-smokers compared to ever smokers.…”
Section: Tumour Characteristicssupporting
confidence: 92%
“…In line with results from most previous studies [7,11,12,16,19,26], never-smokers were older at diagnosis compared to current smokers and former smokers. The observed higher proportion of both younger (<50 years) and older patients (80 years) among never-smoking has, to the best of our knowledge, never been observed before.…”
Section: Patient Characteristicssupporting
confidence: 91%
See 2 more Smart Citations
“…An earlier study has demonstrated that ever-smokers had poorer survival rates than never-smokers, and current smoking was a significant prognostic factor of a poor prognosis in the study population. 10 Similarly, another study by Clément-Duchêne et al 11 opined that improved survival in nonsmokers was probably related to factors like female gender, Asian race, and higher incidence of adenocarcinoma. 11 In a review on "lung cancer in never smokers" by Subramanian and Govindan, 12 it has been shown that adenocarcinoma is the predominant subtype and improved response rates to epidermal growth factor receptor-tyrosine kinase inhibitors 12 like gefitinib and erlotinib in nonsmokers.…”
Section: Discussionmentioning
confidence: 98%